Indian public finances - Bhargava, Rajendra Nath. (London : Allen & Unwin, 1962)
This book explains the objectives of state policy and the criteria to be employed in judging its success. It examines the alternative methods of raising resources for public sector and critically explains the advantages and limitations of each of these
Includes bibliography.
osc 18/07/2018
Loans
Keywords: Public Finance; India